Numerical Investigation of the Effect of Wire Screen Mesh Specification and Evaporator Length on Thermal Performance of Cylindrical Heat Pipe - Hameed, Hassanain Ghani; Rageb, Abudl-Muhsin A. (Basrah Journal for Engineering Sciences, 2014)
A numerical model has been developed to determine the effect of the wire screen mesh (wick) type on the heat transfer performance of copper–water wicked heat pipe. This model represented as steady-state incompressible flow. The governing equations in cylindrical coordinates have been solved in vapor region, wick structure and wall region, using finite difference with forward-backward upwind scheme. The results show that increasing the mesh number led to decreasing the maximum heat transfer limit and increasing the capillary pressure. While, for the same heat input the operating temperature of the heat pipe increase when the mesh number increase. Also, it was found that increasing the evaporation length, with constant condensation length, decrease the operating temperature and increase the maximum heat transfer limit. For verification of the current model, the results of liquid pressure drop for a heat pipe have been compared with the previous study for the same problem and a good agreement has been achieved.